Group Decision Support System Using SMART-COPELAND SCORE Model In Choosing The Best Alternative Pair - Devi Valentino Waas; Made Dona Wahyu Arsitana; I Putu Hendika Permana; I Komang Wiratama; I Gede Iwan Sudipa (Telematika, 2022)
Purpose: Adjust the Group Decision Support System (GDSS) model in completing case studies of selecting the best alternative candidate pairs for the OSIS core board with many decision-makers and problems in the differences in the preferences of decision-makers as well as modeling in decision making with multi-criteria and multi-attributes and combining preferences decision-makers to choose the best alternative partner candidate.Design/methodology/approach: The Group Decision Support System (GDSS) model combines the SMART method for modeling multi-criteria and multi-attribute assessments and the Copeland Score model for aggregating the judgments of five decision-makers against the selected pair of OSIS core board candidates using a voting mechanism.Findings/result: The comparison test for the manual calculation of the SMART- Copeland Score Model method with the results of the system calculation is the same. From the ten alternative data in the first stage of the test through the SMART method calculation, it then passes into four alternatives divided into two alternative candidate pairs, namely alternative candidate pairs (A1, A3) and alternative candidate pairs (A2, A4). The second stage test uses calculations Copeland Score voting, which produces the best alternative candidate pair, namely alternative (A1, A3) with a final point score = 4.Originality/value/state of the art: Based on a review of previous research, this study uses line-up criteria, written tests, and interview tests with the SMART method to calculate alternative scores on each criteria, and the Copeland Score model to aggregate decision makers' preferences to produce the best alternative candidate pairs. In calculating the final value of the alternative ranking.